Tenth of december : stories - Saunders, George, 1958- (2013)
A collection of stories which includes "Home," a wryly whimsical account of a soldier's return from war; "Victory lap," a tale about an inventive abduction attempt; and the title story, in which a suicidal cancer patient saves the life of a young misfit.
Victory lap -- Sticks -- Puppy -- Escape from Spiderhead -- Exhortation -- Al Roosten -- The semplica girl diaries -- Home -- My chivalric fiasco -- Tenth of December.
"The stories in this work were originally published in Harper's Magazine, McSweeney's Quarterly Concern, The New Yorker, and Story Magazine"--Title page verso.
Keywords: Short stories -- 21st century; Short stories, American; United States -- Social life and customs -- 21st century -- Fiction